Interbank linkages and contagion risk in the portuguese banking system - Fernandes, Lara Mónica Machado (2014)
Interbank money markets play a fundamental role in financial systems but they can also be a channel through which problems in one institution can spread to the remaining ones. In particular, the potential for contagion stemming from interbank money markets is closely related with the pattern of interbank lending relationships. In this study, we characterize the Portuguese overnight interbank money market between 1999 and 2009 and analyze its inherent potential for contagion, based on bilateral interbank exposures. We conclude that: (i) the Portuguese overnight interbank money market has a multiple money center structure, where some banks have, simultaneously, an important role as lenders as well as borrowers; (ii) although unlikely, the failure of one institution can have contagion effects, pushing others into failure; (iii) however, even under the most extreme assumptions, banks that fail by contagion represent less than 10 per cent of the total banking systems assets.